Effects of an increased concentrate diet on rumen pH and the bacterial community in Japanese Black beef cattle at different fattening stages - OGATA, Toru (J Vet Med Sci, 2019)
This study evaluated the effects of increasing the proportion of concentrate in the diet on the rumen pH and bacterial community in Japanese Black beef cattle at different fattening stages. Six rumen-cannulated beef cattle were studied in the middle (Mid group, n=3, age 21–22 months) and late (Late group, n=3, age 31 months) fattening stages. The cattle were fed rice straw with control (CON period) or high-concentrate (HC period) diets for 14 consecutive days in each period. Rumen pH was measured continuously and the rumen fluids were collected on the last day of each period. The 24-hr mean and minimum rumen pH in the Mid group were significantly (P<0.05) lower during the HC period compared with the CON period, whereas those in the Late group were continuously low during both periods. In the Late group, the ruminal volatile fatty acid and lactic acid concentrations were significantly (P<0.05) higher during the HC period. During the HC period, the proportions of Prevotella and Caloramator were significantly (P<0.05) higher and lower, respectively, in the Mid group. From these findings, significant changes in the rumen pH and bacterial community induced by dietary changes were mainly observed in the Mid group. Therefore, the ruminal fermentative function in response to a higher concentrate diet might adapt differently in Japanese Black beef cattle at the two different fattening stages.